D- region ionosphere response to the total solar eclipse of 22 July 2009 deduced from ELF- VLF tweek observations in the Indian sector - Singh, Rajesh; Veenadhari, B.; Maurya, A. K.; Cohen, Morris B.; Kumar, Sushil; Selvakumaran, R.; Pant, P.; Singh, Abhay K.; Inan, Umran S. (My University, 2011)
Observations of tweeks with higher harmonics (n > 1) at low latitude stations Allahabad and Nainital, in the Indian sector, during the total solar eclipse on 22 July 2009, are presented. Allahabad and Nainital stations were in 100% and 85% of the totality paths. Observations suggest that about 30â€“40% obscuration of solar disc can lead to the tweeks occurrence which otherwise occur only in nighttime. A total of 148 tweeks at Allahabad and 20 tweeks at Nainital were recorded with some of them up to 3rd harmonics. The World Wide Lightning Location Network data indicated that tweeks observed were generated by lightningâ€™s located in the partial eclipse area of Asiaâ€ Oceania region. The changes in Dâ€ region ionospheric VLF reflection height and electron density (âˆ¼22â€“23 cmâˆ’3) during eclipse have been estimated from the first cutâ€ off frequency of the tweeks. The reflection height increased from âˆ¼89 km from the first occurrence of tweek to about 91â€“92 km at the totality and then decreased to âˆ¼87 km at the end of the eclipse, suggesting a change of about 5 km in the reflection height during eclipse. The reflection heights are lower by 2â€“3 km as compared to normal nighttime tweek reflection heights. The above increase in the reflection height indicate that the partial nighttime condition is created during eclipse, as the main Dâ€ region ionizing radiation Lyman a is blocked but solar soft Xâ€ ray and EUV radiations originating from the limb solar corona are not totally blocked which produce some of ionization in the Dâ€ region.
Keywords: D-region ionosphere; Solar eclipse; ELF; VLF; Tweeks; Allahabad; Nainital; Solar radiation variations